From Nothing to Something: Study on How Local Government Transformed Oil and Gas Area into Ecotourism Village in Indonesia through Branding Strategy - PRAYUDI, PRAYUDI; ARDHANARISWARI, Kartika Ayu (Journal of Environmental Management and Tourism; Vol 9 No 8 (2018): JEMT Volume IX Issue 8(32) Winter 2018DO - 10.14505//jemt.v9.8(32).15, 2019)
This study aims to analyse how Bojonegoro District Government in Indonesia applied branding strategy for oil and gas area in Wonocolo Village. This village has a unique atmosphere of traditional petroleum mining. Government, villagers and state oil company discussed on how to change and add value to this village through branding strategy. Branding strategy involves creating, developing, implementing and managing brands continuously until the brand becomes strong. Using qualitative research methods, this study describes how the steps undertaken in the village that formerly was full of old oil wells, into a new tourist area that has economic value. The result of the research shows that there were three stages done in branding Wonocolo as an ecotourism village. They include identification of village uniqueness, creation of brand identity and brand message. The biggest challenge in this branding strategy was to change the mindset of Wonocolo villagers that turning the old oil wells village into an ecotourism destination can provide economic benefit.